A novel antimicrobial peptide derived from human BPIFA1 protein protects against Candida albicans infection. Issue 2 (February 2022) - Hu, Nan; Mo, Xi-Ming; Xu, Shi-Na; Tang, Hao-Neng; Zhou, Ying-Hui; Li, Long; Zhou, Hou-De
Bactericidal/permeability-increasing fold containing family A, member 1 (BPIFA1) is an innate immunity defense protein. Our previous studies proved its antibacterial and antiviral effects, but its role in fungi remains unknown. The study aimed to identify antifungal peptides (AFP) derived from BPIFA1, and three antimicrobial peptides (AMP1–3) were designed. The antifungal effects were proved by growth inhibition assay. AMP3 activity was confirmed by germ tube growth experiment and XTT assay. Its effects on cell wall and membrane of Candida albicans were assessed by tannic acid and Annexin V-FITC/PI double staining, respectively. Additionally, scanning electron microscope (SEM) and transmission electron microscopy (TEM) were used for morphological and ultrastructural observation. The expression of ALS1, EAP1, and SUN41 was tested by qPCR. Ultimately, three AMPs could fight against C. albicans in vitro, and AMP3 was highly effective. It functioned by destroying the integrity of cell wall and normal structure of cell membrane. It also inhibited biofilm formation of C. albicans . In addition, AMP3 down-regulated the expression of ALS1, EAP1, and SUN41, those are known to be involved in virulence of C. albicans . Altogether, the study reported successful development of a novel AFP, which could be used as a new strategy for antifungal therapy.